4iPay: modelo para sistemas de pagamento móvel em comércio ubíquo - Roehrs, Alex (Universidade do Vale do Rio dos Sinos, 2012)
This work aims at presenting a usability and architectural model for a mobile payment system. In our model, we assume independence of devices, of location, of mobile operator, and of administrator, to allow all kinds of payment in ubiquitous environments (Ubiquitous Commerce). In this work, we begin describing motivation, goals, and fundamental concepts, in which the proposed model is based. Next, we present related works and a detailed comparative analysis of those projects, deriving the most important features. Later, we propose a model of mobile payment, called 4iPay, based on those features. We detail the 4iPay model, architecture, features, and the technical-scientific proposal of an electronic commerce system in ubiquitous environments. We consider, in the proposed model, the convergence of various related works in terms of ubiquity, unity, universality, and unison. Thus, 4iPay aims at bringing together the best features, innovating and improving in some aspects. In the model, we propose a distinguished solution in terms of architecture, business model, usability, low bandwidth consumption and high performance in payment and receipt transactions. We also consider issues such as device independence, physical location, security and reliability, and other features related to mobile electronic commerce transactions, such as optimizing communications protocols usage and flexibility in local or remote connections. We also present the effective use in scenarios of where and how 4iPay can be applied. For this purpose we present the prototype developed to evaluate the model. Finally, we present the scenarios assessment results, the application performance evaluation and the proposed model acceptance survey.
Keywords: Sistema de pagamento móvel; Comércio ubíquo; Carteira digital; Comércio móvel; Computação ubíqua; Computação móvel; Ubiquitous computing; Mobile computing; Mobile payment system; Ubiquitous commerce; Digital wallet; Mobile commerce; Near-field communication; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação